2009
DOI: 10.1002/ppul.20971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Hypercapnia in the Neonatal Mouse Lung and Brain

Abstract: Exposure to chronic hypercapnia may lead to early initiation of alveolar budding in the neonatal mouse, but may also lead to increased TUNEL-positive cells in the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In neonatal mice, chronic exposure to 8% CO 2 from birth has been reported to induce changes in lung morphology consistent with accelerated maturation, including thinning of alveolar walls and increased secondary septation (13). Taken together, these observations sound a note of caution that the risks vs. benefits of chronic hypercapnia for long-term lung development, function, and susceptibility to lung injury remain unclear and require further study.…”
Section: Discussionmentioning
confidence: 77%
“…In neonatal mice, chronic exposure to 8% CO 2 from birth has been reported to induce changes in lung morphology consistent with accelerated maturation, including thinning of alveolar walls and increased secondary septation (13). Taken together, these observations sound a note of caution that the risks vs. benefits of chronic hypercapnia for long-term lung development, function, and susceptibility to lung injury remain unclear and require further study.…”
Section: Discussionmentioning
confidence: 77%
“…Increased cortical neuronal nuclei apoptosis was described in hypercapnic (PaCO 2 > 65 mm Hg) newborn pigs ( 33 ). Das et al ( 34 ) demonstrated increased TUNEL-positive cells in developing brain of neonatal mouse pups exposed to chronic hypercapnia (6 days exposed to 8% CO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased arterial carbon dioxide levels have been associated with beneficial effects after experimental brain injury in the past. [2][3][4] The effects of mild respiratory acidosis in prevention as well as recovery from organ system damage have previously been studied in the heart, lung, and immune systems, [5][6][7][8][9] and permissive hypercapnia is part of today's clinical practice of low tidal volume ventilation to improve the outcome of patients with acute lung injury. 10 Interestingly, the current American Heart Association Guidelines recommend 12-15 breaths/min during cardiopulmonary resuscitation and stress the potential negative role of inadvertent hyperventilation on survival.…”
Section: "Therapeutic Hypercapnia" After Ischemic Brain Injurymentioning
confidence: 99%